Kebermaknaan Hidup, Kestabilan Emosi dan Depresi - Perwito Utomo, R Hendro Rumpoko; Meiyuntari, Tatik (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
The purpose of this study was to examine the relationship between Meaningin Life and Emotional Stability at depression level. Subjects were students who enterthe category of early adulthood (19-25 years) in Yogyakarta. Number 93 researchsubjects. Regression analysis showed: (1) here was a significant relationship betweenemotional stability, Meaning in Life and Depression level , with a coefficient F =17.494 , p = 0.000 ; p < 0.05 ( 2 ) obtained regression line equation is Y = 106.2120421x1 - x2 0511 , where Y is the Depression , X1 and X2 are Meaning in Life isEmotional Stability . Negative coefficient in Meaning in Life and Stability Emotionsgive meaning or effect the opposite relationship with Depression . If Meaning in Lifeand Emotional Stability increases, the depression will decrease and vice versa if theMeaning in Life and Emotional Stability decreased it will increase the Depression